2007
DOI: 10.1620/tjem.213.313
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Visual Deficits Tested by Visual Evoked Potentials in Streptozotocin-Induced Diabetic Rats

Abstract: Visual evoked potentials (VEP) can be used as an objective non-invasive method to study the electrical activity of the visual system. Latency and amplitude measurements of VEP demonstrated that diabetes mellitus has been associated with increases in the latencies whereas the amplitude measurements revealed contradictory results. Although physical exercise has been reported to reduce the complications of diabetes mellitus, the effect of exercise on the visual system remains unknown. We investigated the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Diabetes was induced by injection of streptozotocin (STZ) as described by Ozkaya et al (Ozkaya et al 2007). Rats were fasted for 12 hours before a single intraperitoneal injection of STZ (60 mg/kg; Sigma Co., USA) dissolved in citrate buffer (0.1 mol/L; pH 4.5).…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…Diabetes was induced by injection of streptozotocin (STZ) as described by Ozkaya et al (Ozkaya et al 2007). Rats were fasted for 12 hours before a single intraperitoneal injection of STZ (60 mg/kg; Sigma Co., USA) dissolved in citrate buffer (0.1 mol/L; pH 4.5).…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…Th ey received an intraperitoneal (i.p.) injection of streptozotocin (STZ) 60 mg/kg BW dissolved in 0.1 mol/l citrate buff er (pH 4.5) aft er fasting for 12 h (Ozkaya et al 2007). Control groups received an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…As an early marker of visual system deficits observed in diabetic state, visual evoked potential (VEP) latencies were measured in STZ-induced diabetic rats in our laboratories. The results of the previous studies were demonstrated that visual evoked potential (VEP) latencies were prolonged in STZ-induced diabetic rats whereas the latencies were restored by moderate physical exercise [60,141,142]. The VEP alterations were found to be accompanied with the increased TBARS concentration in the brain tissues of the diabetic rats.…”
Section: Diabetic Neuropathymentioning
confidence: 97%